Seismic Expression of Paleogene Talangakar Formation - Asri & Sunda Basins, Java Sea, Indonesia - Dwandari Ralanarko; Deni Wahyuadi; Pranowo Nugroho; Wrahaspati Rulandoko; Ildrem Syafri; Abdurrokhim Almabrury; Andi Agus Nur (Ikatan Ahli Geologi Indonesia, 2020)
The Asri and Sunda Basin are located offshore Southeast Sumatra under the SE Sumatera Production Sharing Contract (PSC). Currently, Pertamina Hulu Energi OSES operates in the Asri and Sunda Basins, known as Southeast Sumatra (SES) Block. As one of Indonesian prime oil and gas producing area in the past 50 years, these basins have produced cumulatively more than 1,500 MMBOE with an average of 90,000 BOPD. Both Asri and Sunda Basins are part of a series of Cenozoic half grabens developed on the Asian continental margin, that have occupied a retro arc setting since early Neogene times.Hydrocarbon exploration activities in the offshore southeastern Sumatra began with a signed agreement of Contract Sharing between IIAPCO (Independent Indonesian American Petroleum Company) and Pertamina on 6 September 1968.The contract area included the offshore areas east of Sumatra and south of Bangka - Belitung Islands, covering an area of 124,000 km2. After the final relinquishment in 2008, the current PSC boundary covers an area of 5,851 km2.This paper presents the results of integrated petroleum geosciences framework, its implications for Oligo-Miocene reservoirs and hydrocarbon prospectivity of the basins using near field exploration approaches. A four-fold division comprising rift initiation, rift climax, immediate post rift and late-post rift stages of basin evolution characterize the basin filling. Seismic expression of these kinematic units gives an idea about the linkage of their deposition with different stages of rift evolution. The present study has also identified a new potential play concept in Oligo -Miocene reservoirs.